Occurrence of major complications after cochlear implant surgery in Ireland. (2nd November 2018) - Petersen, Hannes; Walshe, Peter; Glynn, Fergal; McMahon, Rosemary; Fitzgerald, Conall; Thapa, Jyoti; Simoes-Franklin, Cristina; Viani, Laura
Abstract : Objectives: Cochlear implantation (CI) is considered an effective and relatively safe procedure for patients with severe-profound hearing loss. However, severe complications are reported in several studies. The purpose of this study was to report the frequency and management of major complications following CI surgery at the National CI Programme (NCIP) in Ireland. Methods: Major complications were defined according to the classification of Hansen et al . 2010. The medical records of 1017 patients undergoing CI between 1995 and 2016 were analyzed retrospectively for major complications. In addition, radiological and intraoperative findings as well as therapeutic management of all patients with a major complication were reviewed. Results: Altogether, 1017 patients underwent 1266 CI surgeries. The median follow-up of all CI surgeries was 44 months. The total number of major complications identified was 21 which corresponds to an overall rate of 1.7%. The majority of major complication (71%) occurred at least one week after surgery. The most common major complications were internal receiver/stimulator protrusion and migration (6/21), followed by migration of the electrode array (4/21) and recurrent otitis media requiring re-implantation (4/21). All patients with major complications required additional surgery, with reimplantation necessary in 19 patients (90%). Discussion : CI surgery is a safe surgical procedure for hearing rehabilitation associated with a low rate of severe complications. However, major complications can occur many years after surgery, making revision surgery necessary. Conclusion: Long-term follow-up is necessary for the early identification of complications to facilitate appropriate care.